The spectra of $$p\bar{Λ }$$ p Λ ¯ and $$p\bar{Σ }$$ p Σ ¯ hexaquark states - Xuan-Heng Zhang; Sheng-Qi Zhang; Cong-Feng Qiao (European Physical Journal C: Particles and Fields)
Abstract Motivated by the recent observation of the $$J^P = 1^+$$ J P = 1 + resonance X(2085) in the $$p\bar{Λ }$$ p Λ ¯ system by the BESIII collaboration, we study the molecular states of $$p\bar{Λ }$$ p Λ ¯ and $$p\bar{Σ }$$ p Σ ¯ with baryon-antibaryon structures within the framework of the QCD sum rules. Non-perturbative contributions up to dimension 13 in quark operator expansion (OPE) are considered. Our calculation results indicate the possible existence of six $$p\bar{Λ }$$ p Λ ¯ and $$p\bar{Σ }$$ p Σ ¯ molecular states with quantum numbers $$J^{P}=0^{-}, 0^{+}, 1^{-}$$ J P = 0 - , 0 + , 1 - , which do not support X(2085), or at least not its main component, being a $$p\bar{Λ }$$ p Λ ¯ or $$p\bar{Σ }$$ p Σ ¯ molecular state. Additionally, the previously observed state X(2075) also lies in the vicinity of $$p\bar{Λ }$$ p Λ ¯ and $$p\bar{Σ }$$ p Σ ¯ molecular states, and its inner structure might not be entirely transparent, rather possibly a mixture of tetraquark and hexaquark states. The possible decay modes of the concerned states are analyzed.